Telaah Kritis Makna Hujan dalam Alquran - Arif Iman Mauliddin (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This article examines the meaning of the word rain in the Qur'an. Rain can be interpreted as a blessing bearer, but for some people, rain also interpreted as a disaster, whereas the benefits of rain is very great for life on earth. Research based on the interpretation of Ibn Kathir, Quraish Shihab, and HAMKA by using comparative method. This research found that the word of rain in the Qur'an not only means “rahmat” or gift, but also meaningful as doom or disaster, and natural phenomena. The equation of the three interpretations is that rain is seen as a “rahmat” or a gift because it is considered beneficial for all creatures on the earth, the rain is considered as a punishment because it is held down by God for some time and also because of the descent accompanied by thunder and heavy wind that can damage the earth, and rain as a natural phenomenon because as a process of descending water from sky to earth.